2019
DOI: 10.21203/rs.2.11549/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LINC01534 promotes the aberrant metabolic dysfunction and inflammation in IL-1β-simulated osteoarthritic chondrocytes by targeting miR-140-5p

Abstract: Backgrounds: Long non-coding RNA 01534 (LINC01534) is highly expressed in the tissues of patients with osteoarthritis (OA). This study investigated the mechanism of LINC01534 on abnormal metabolic dysfunction and inflammation in OA chondro-cytes induced by IL-1β. Methods: The quantitative Real-Time PCR (qRT-PCR) was used to determine the expressions of LINC01534, aggrecan, collagen II and matrix metalloproteinase (MMPs) in OA cartilage tissue or OA chondrocyte model induced by IL-1β. The ex-pressions of aggrec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…BST2 promoted cell growth in renal cell carcinoma 52 and oral cavity cancer 53–54 . LINC01534 has been reported that highly expressed in the tissues of patients with osteoarthritis 55 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BST2 promoted cell growth in renal cell carcinoma 52 and oral cavity cancer 53–54 . LINC01534 has been reported that highly expressed in the tissues of patients with osteoarthritis 55 …”
Section: Discussionmentioning
confidence: 99%
“…[53][54] LINC01534 has been reported that highly expressed in the tissues of patients with osteoarthritis. 55 KEGG was annotated and enriched by the significant results in the comparison of group differential genes. The results showed that the three groups of differential gene pathways mainly concentrated in the signal transduction pathway.…”
Section: Discussionmentioning
confidence: 99%